Efficacy of honey nasal spray as an adjunct treatment for allergic rhinitis : a randomized controlled trial - Manab, Farah Wahida Abd (2017)
BACKGROUND Allergic rhinitis is an IgE-mediated inflammation of the nasal mucosa. The management of allergic rhinitis has not changed much and only limited studies has been done to explore the benefit of complementary alternative therapy. Honey is proven in its anti-inflammatory, antibacterial and anti-oxidant properties and found to be useful for treatment of inflammation. We aimed to determine the efficacy of honey nasal spray as an adjunct treatment of moderate to severe persistent allergic rhinitis. METHOD Patients were recruited from our Otorhinolaryngology- Head & Neck Surgery Clinic from November 2015 to July 2016. Thirty moderate to severe persistent allergic rhinitis patients with positive skin prick tests were divided randomly into control and trial group. Both groups received standard medication (intranasal corticosteroids and oral antihistamines). In addition, the trial group received honey nasal spray as adjunctive daily dose. Patients were assessedusing SNOT22 questionnaires at 0, 2nd and 6th weeks of the study with the focus on the primary symptoms of nasal blockage, rhinorrhea and sneezing RESULTS There was overall improvement of total SNOT 22 score and each symptom score of nasal blockage, rhinorrhea and sneezing together with the total serum IgE level in both groups at the end of 6 weeks. However, the improvement was seen more consistently in the trial group as evidenced by the reduction of estimated means score of all measured outcomes. CONCLUSION The honey nasal spray has beneficial effect as an adjunct treatment in moderate to severe persistent allergic rhinitis by acting as a protective mucous layer in reducing the attachment of allergen to the nasal mucosa.